PERBANDINGAN TINGKAT LOYALITAS TERHADAP MEREK PADA PENGGUNA SMARTPHONE BERDASARKAN TEORI KEPRIBADIAN BIG FIVE FACTORS OF PERSONALITY - Rury ST. Ruhaniah (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract This study aims to know whether there is comparative of brand loyalty degree based on theory Big Five Factors of Personality on smart-phone user. The level of brand loyalty formed based on brand loyalty pyramid by David A. Aaker (1991) that having a certain characteristics on each level of brand loyalty. Research conducted by involving 142 smartphone user that settle in Jakarta. An instrument consisting of two research scale, the level of brand loyalty scale and personality scale that adopted from personality scale of International Personality Item Pool (IPIP) which based on NEO-PI R. Hypotheses tested by chi square analyze with the assistance program SPSS ver 17.0 for Windows. Based on the analysis result of data that has been done obtained chi square of personality variable is 58,070, degree of freedom is 4 with p-value 0.00 < 0.05, chi square of brand loyalty level variable is 15,958, degree of freedom is 4 with pvalue 0.03 < 0.05. This means that the null hypothesis is rejected and the alternative hypothesis is accepted, then there is a significant comparison of levels of brand loyalty based on the theory the Big Five Factors of Personality on the smart-phone user. Keywords: Brand Loyalty Personality, Big Five Factors, Smartphone, NEO-PI R